"Between a rock and the mitral valve space": Transcatheter mitral valve‐in‐valve implantation for paravalvular leak and refractory hemolysis complicated by circumflex coronary occlusion. Issue 1 (6th November 2019) - Adams, Heath S. L.; Rajani, Ronak; Hildick‐Smith, David; Redwood, Simon
Abstract: Transcatheter mitral valve implantation (TMVI) is an emerging field in structural cardiology. A particularly difficult group to treat is high‐risk patients requiring valve in mitral annular calcification (ViMAC) intervention, with overall poor procedural success and outcomes in recent registries. This case highlights an unusual complication of paravalvular regurgitation (PVL) through the uncovered stent frame of a balloon expandable transcatheter heart valve (THV) on the left ventricular side of the prosthesis, leading to mechanical hemolysis and subsequent anuric renal failure post a ViMAC procedure. Attempts to treat the PVL with an occlusion plug device were unsuccessful and led to left circumflex coronary occlusion secondary to mechanical compression of the vessel in the posterior mitral valve annulus, a previously unreported phenomenon. A repeat valve‐in‐valve procedure was performed to treat the PVL, and immediate angioplasty resolved the left circumflex occlusion. High‐risk patients requiring TMVI pose multiple challenges to Heart Teams in the treatment of valve pathology. Optimal procedural planning, multimodality imaging, improved THVs, and the awareness of potential complications are fundamental in overcoming the learning curve of TMVI and improved outcome for patients requiring ViMAC.